Expert Recommendation System To Promote Development-Focused Universities - Bayraktar, Mehmet Yasar; Kaya, Mehmet (My University, 2024)
With the support given to university education in recent years, newly opened or developing universities are trying to specialize in various fields within the framework of the regional development mission. In order to achieve success, there is always a need for experts -who do successful studies and have a wide perspective- in the field sought. Reaching candidates who are experts in their field is a difficult process since it cannot be expressed with a linear/linear mathematical formula. In particular, the increasing number of recent studies, articles and reports has made the selection of experts on the subject difficult and systems that automatically find experts are needed. Reaching candidates who are experts in their field is a difficult process since it is relative. In particular, the increasing number of recent studies, articles and reports has made the selection of experts on the subject difficult and systems that automatically find experts are needed. With this study, the scientific studies published by the academicians and the co-authors in the studies will be evaluated and expert candidates \"suitable for the criteria sought\" will be listed. Results will be given on the basis of scoring scientific studies for the appropriate researcher criteria. To evaluate a researcher's score, an object function of the expert will be made by looking at the filtered keywords over the articles and studies written by that person. In this application, using the 'Dergi Park' database, suitable expert candidates were scored for the filtered words.
Keywords: Finding Experts; Automatic Candidate Selection; Expert Suggestion